Sorbitol treatment extends lifespan and induces the osmotic stress response in Caenorhabditis elegans - Chandler-Brown, Devon; Choi, Haeri; Park, Shirley; Ocampo, Billie R.; Chen, Shiwen; Le, Anna; Sutphin, George L.; Shamieh, Lara S.; Smith, Erica D.; Kaeberlein, Matt (Frontiers in Genetics, 2015)
The response to osmotic stress is a highly conserved process for adapting to changing environmental conditions. Prior studies have shown that hyperosmolarity by addition of sorbitol to the growth medium is sufficient to increase both chronological and replicative lifespan in the budding yeast, Saccharomyces cerevisiae. Here we report a similar phenomenon in the nematode Caenorhabditis elegans. Addition of sorbitol to the nematode growth medium induces an adaptive osmotic response and increases C. elegans lifespan by about 35%. Lifespan extension from 5% sorbitol behaves similarly to dietary restriction in a variety of genetic backgrounds, increasing lifespan additively with mutation of daf-2(e1370) and independently of daf-16(mu86), sir-2.1(ok434), aak-2(ok524), and hif-1(ia04). Dietary restriction by bacterial deprivation or mutation of eat-2(ad1113) fails to further extend lifespan in the presence of 5% sorbitol. Two mutants with constitutive activation of the osmotic response, osm-5(p813) and osm-7(n1515), were found to be long-lived, and lifespan extension from sorbitol required the glycerol biosynthetic enzymes GPDH-1 and GPDH-2. Taken together, these observations demonstrate that exposure to sorbitol at levels sufficient to induce an adaptive osmotic response extends lifespan in worms and define the osmotic stress response pathway as a longevity pathway conserved between yeast and nematodes.